The amazing world of arbitration - Moens, Gabriel; Evans, Philip (Murdoch University, 2012)
This is a review article of Commercial Arbitration in Australia, written by the President of the Australian Centre for International Commercial Arbitration (ACICA), Professor Doug Jones. The article provides an overview of the themes discussed in the book and concentrates on the Commercial Arbitration Act 2010 (NSW). In particular, the article reviews the power of arbitral tribunals to order interim measures of protection, and discusses arb-med processes under section 27D of the Act. In addition, the authors discuss the importance of the new NSW legislation on building and construction law.